Update to NCAA bylaw raises concerns about impact on student‐athletes' mental health. Issue 5 (August 2015) - Neal, Timothy; Sullivan, John P.; Coppel, David B.; Maniar, Sam; Baillie, Patrick; Quandt, Eric F.
<x xml:space="preserve">Abstract</x> A recent update to a National Collegiate Athletic Association bylaw related to sport psychology raises significant concerns about providing student‐athletes sufficient care to ensure their long‐term health and well‐being. The changes also raise the potential liability risk for institutions and threaten confidentiality protection for student‐athletes.